Examining the Neural Markers of Speech Rhythm in Silent Reading Using Mass Univariate Statistics of EEG Single Trials - Stephanie J. Powell; Srishti Nayak; Cyrille L. Magne (Brain Sciences)
Background/Objectives: The Implicit Prosody Hypothesis (IPH) posits that individuals generate internal prosodic representations during silent reading, mirroring those produced in spoken language. While converging behavioral evidence supports the IPH, the underlying neurocognitive mechanisms remain largely unknown. Therefore, this study investigated the neurophysiological markers of sensitivity to speech rhythm cues during silent word reading. Methods: EEGs were recorded while participants silently read four-word sequences, each composed of either trochaic words (stressed on the first syllable) or iambic words (stressed on the second syllable). Each sequence was followed by a target word that was either metrically congruent or incongruent with the preceding rhythmic pattern. To investigate the effects of metrical expectancy and lexical stress type, we examined single-trial event-related potentials (ERPs) and time–frequency representations (TFRs) time-locked to target words. Results: The results showed significant differences based on the stress pattern expectancy and type. Specifically, words that carried unexpected stress elicited larger ERP negativities between 240 and 628 ms after the word onset. Furthermore, different frequency bands were sensitive to distinct aspects of the rhythmic structure in language. Alpha activity tracked the rhythmic expectations, and theta and beta activities were sensitive to both the expected rhythms and specific locations of the stressed syllables. Conclusions: The findings clarify neurocognitive mechanisms of phonological and lexical mental representations during silent reading using a conservative data-driven approach. Similarity with neural response patterns previously reported for spoken language contexts suggests shared neural networks for implicit and explicit speech rhythm processing, further supporting the IPH and emphasizing the centrality of prosody in reading.